Microalgae: A potential alternative to health supplementation for humans - Apurav Krishna Koyande; Kit Wayne Chew; Krishnamoorthy Rambabu; Yang Tao; Dinh-Toi Chu; Pau-Loke Show (Food Science and Human Wellness)
Microalgae has been consumed in human diet for thousands of years. It is an under-exploited crop for production of dietary foods. Microalgae cultivation does not compete with land and resources required for traditional crops and has a superior yield compared to terrestrial crops. Its high protein content has exhibited a huge potential to meet the dietary requirements of growing population. Apart from being a source of protein, presence of various bio-active components in microalgae provide an added health benefit. This review describes various microalgal sources of proteins and other bio-active components. One of the heavily studied group of bio-active components are pigments due to their anticarcenogenic, antioxidative and antihypertensive properties. Compared to various plant and floral species, microalgae contain higher amounts of pigments. Microalgal derived proteins have complete Essential Amino Acids (EAA) profiles and their protein content is higher than conventional sources such as meat, poultry and dairy products. However, microalgal based functional foods have not flooded the market. The lack of awareness coupled with scarce incentives for producers result in under-exploitation of microalgal potential. Application of microalgal derived components as dietary and nutraceutical supplements is discussed comprehensively. Keywords: Health, Human, Microalgae, Protein, Supplement